Mise en tourisme d’un village shui dans la province montagneuse du Guizhou (sud de la Chine) : imaginaires et instrumentalisation politique du paysage - Evelyne Gauché (Revue de Géographie Alpine)
This contribution questions the build-up of touristic imaginaries, through the tourismification of a Shui village located in the mountainous Province of Guizhou (China). The growth of the tourism industry in the rural areas driven by the State in the early 1980s, has been going on according to a highly standardised official model. Not only did it aim at fostering economic development, but also at making up national identity. It is founded on a stereotyped vision of the landscape, seen through the prism of the Mandarin ideal based on poetry, gardening and pictorial arts or Shanshui, literally ‘mounts and waters’, as well as on the folklorisation of ethnic minorities and the modernisation of the countryside. As such, it uses both landscape and populations as tools, through a national narrative of the greatness of the Chinese nation and the Han people with, in the background, the praise of the socialist ideal. Correlatively to the projection of Han imaginaries onto the daily landscape of the Shui, the social representations of this landscape are also transformed by tourism, thereby revealing how the Shui population is adhering to the State model.